Daisy 1, 2, 3 - Catalanotto, Peter (Atheneum Books for Young Readers, 2003)
Mrs. Tuttle teaches a dog obedience class to 20 Dalmatians who are all named Daisy, but each one has unique characteristics based on the numbers one through twenty.